Museum Bali Archaeological Artifacts Learning Video Based on Inquiry Learning Method in Social and Science Subject for Fourth Grade Elementary Schools - I Nyoman Windhu Wiguna; A.A Gede Agung; A.A Ayu Dewi Sutyaningsih (Universitas Pendidikan Ganesha, 2025)
The use of instructional media plays a vital role in creating an innovative and engaging classroom environment. However, many teachers still face challenges in developing media that actively support student participation. This study aims to develop and evaluate the quality and effectiveness of an inquiry-based learning video for the IPAS subject, specifically on the topic “My Living Area in the Past.” The research employed a development model using the ADDIE framework. The participants included subject matter experts, instructional design experts, media experts, and fourth-grade elementary school students as end users. Data were collected using expert validation questionnaires, individual and small group trials, and multiple-choice objective tests. The data analysis techniques involved descriptive quantitative analysis and dependent sample t-tests. The results showed that the instructional video was rated as excellent in terms of structure, content, instructional design, and media quality. The small group trial achieved a practicality percentage of 96.11% (categorized as very good). The dependent t-test analysis revealed a t-value of 16.305, which exceeded the critical value, indicating a significant difference between pre- and post-test scores. These findings conclude that the inquiry-based instructional video is effective in enhancing students’ understanding of the IPAS subject matter. The implications of this study highlight the importance of integrating innovative, inquiry-based media into classroom practices to promote students’ critical thinking and conceptual understanding.